The Antecedents of Food Variety-Seeking Behavior - Hutabarat, Moses; Anggraini, Syifa Tria (Business and Entrepreneurial Review, 2024)
This study aims to analyze the influence of factors such as Regulatory Focus, Food Neophobia, and Psychological Safety on Food variety-seeking behavior among Indonesian tourists. Data from 220 respondents who met the minimum age criteria of 18 years and had a history of travel in Indonesia in the past year were collected through an online questionnaire. The study results show that regulatory focus has a significant favorable influence on food variety seeking. In contrast, tourists with a high regulatory focus tend to be more daring to try new food variations. Meanwhile, food neophobia hurts food variety seeking, suggesting that fear of new foods can inhibit the desire to try food varieties. Furthermore, psychological safety has been proven to positively influence food variety seeking, indicating that psychological safety can encourage tourists to be more courageous in exploring food varieties. This study provides new insights into the factors affecting food variety-seeking behavior among Indonesian tourists. These findings can be used by tourism and culinary industry players to design strategies that can attract tourists to explore culinary diversity. In addition, the results of this research also contribute to the development of literature in business management and marketing, especially those related to consumer behavior in the context of culinary tourism.